Ecotels- a Way to Green Sustainable Tourism - Ankit Prakash; Vikas Sharma (PT FORMOSA CENDEKIA GLOBAL, 2023)
The global traveler's attention has shifted away from crowded cities with high-rise hotels and towards remote locations with a tranquil natural setting that doesn't harm the local ecology. Given the aforementioned information, hoteliers must immediately change their practises and trends in commercial hospitality in relation to the environment. The notion of eco hotels or green hotels has evolved as a result of growing environmental awareness. A